The Transformation of Land Law in Indonesia: From Commodification to Maqāṣid and Social Justice - Firman Muntaqo; Mashudi Mashudi; Alip Dian Pratama; Abdullah Rosikh Fil Ilmi; Iza Rumesten (Al-Ahkam, 2025)
This article examines the transformation of Indonesian land law from the paradigm of fundamental justice embodied in the 1960 Basic Agrarian Law (UUPA) to a market-oriented framework shaped by the Omnibus Law on Job Creation and decentralization policies. This shift generates tensions between constitutional mandates, Pancasila values, customary law, and politico-economic interests that often marginalize structural justice. The study aims to analyze how these foundational values interact with Islamic legal philosophy through the maqāṣid approach to construct a more equitable and sustainable agrarian system. Employing a qualitative normative legal method combined with interpretive and comparative analysis, the research finds that a dialogical integration of UUPA principles, maqāṣid, and the social function of land can generate an alternative paradigm of land governance. The novelty lies in proposing a model emphasizing tawāzun (balance), ecological protection, and social equality. Theoretically, the article enriches global law-and-development discourse, while practically providing normative grounds for reconstructing agrarian policy toward justice and sustainability.